Liberalisation and higher education in India - Mukhopadhyay, Asok (1996)
Giving briefly the background and rationale of liberalisation process in India, the author strongly endorses its extension to higher education in India to remedy the present dismal scenario signified by inverse relationship between rising costs and standards, indifference of teachers and their indulge in private coaching, faculty-UGC role, prevalence of nepotism and political interference, etc. He expects liberalisation to facilitate: autonomy and debureaucratisation, government-private sector funding for R&D, continued evaluation of performance award-accountability linkage and better serving of interests of students and society. - Reproduced
Keywords: Liberalization - India; Education, Higher - India; Educational planning